Prediction of long-term energy consumption trends under the New National Urbanization Plan in China. (10th November 2017) - Yang, Shuncheng; Shi, Longyu
Abstract: According to the National New Urbanization Plan (2014), China's national urbanization rate will reach approximately 60% in 2020. Throughout the rapid process of urbanization, China's energy consumption will expand at an unprecedented rate. In 2012, total energy consumption in China was 3 . 411 × 10 9 tons of coal equivalent (tce); energy shortage is becoming increasingly serious. In this study, two future urbanization scenarios in China were simulated based on linear and logistic growth models. These models were used to quantitatively predict the long-term (2020–2030) energy consumption of urban and rural residents in three economic sectors: transport, construction, and residential. The annual area of newly paved roads in Chinese cities was positively correlated with energy consumption by the transport sector, and the annual increase in newly built floor space in buildings was positive correlated with energy consumption by the construction sector. If the urbanization level of China is in accordance with the new urbanization plan (the logistic growth model), which proposes a lower urbanization speed, the energy consumption growth by the three sectors will be significantly reduced compared with the linear growth model. Energy consumption growth by the transport, construction, and residential sectors will decrease by 7 . 26 × 10 7 tce, 1 . 28 × 10 7 tce, and 5 . 45 × 10 6 tce by 2020.